Stress counselling : a rational emotive bihaviour approach - Gordon, Jack.; Neenan, Michael.; Palmer, Stephen.; Ellis, Albert. (Cassell, 1997)
This book provides people with a conceptual framework and a scientific method of rational thought to help lessen their distress and achieve their personal goals.